2016
DOI: 10.2196/jmir.6362
|View full text |Cite
|
Sign up to set email alerts
|

Role of Psychosocial Factors and Health Literacy in Pregnant Women’s Intention to Use a Decision Aid for Down Syndrome Screening: A Theory-Based Web Survey

Abstract: BackgroundDeciding about undergoing prenatal screening is difficult, as it entails risks, potential loss and regrets, and challenges to personal values. Shared decision making and decision aids (DAs) can help pregnant women give informed and values-based consent or refusal to prenatal screening, but little is known about factors influencing the use of DAs.ObjectiveThe objective of this study was to identify the influence of psychosocial factors on pregnant women’s intention to use a DA for prenatal screening f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 95 publications
2
28
0
Order By: Relevance
“…In this larger initiative, our overarching aim was to produce a DA to foster SDM in the context of prenatal screening for Down syndrome. Our study complements a similar survey of the intentions of pregnant women to use a DA for decisions about prenatal screening for Down syndrome [ 29 ]. We obtained ethics approval from the research ethics boards of the Centre de Santé et de Services Sociaux de la Vieille-Capitale (#2013-2014-29) and the CHU de Quebec (#B14-02-1929).…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…In this larger initiative, our overarching aim was to produce a DA to foster SDM in the context of prenatal screening for Down syndrome. Our study complements a similar survey of the intentions of pregnant women to use a DA for decisions about prenatal screening for Down syndrome [ 29 ]. We obtained ethics approval from the research ethics boards of the Centre de Santé et de Services Sociaux de la Vieille-Capitale (#2013-2014-29) and the CHU de Quebec (#B14-02-1929).…”
Section: Methodsmentioning
confidence: 91%
“…These results are congruent with previous studies showing high levels of intention among health professionals to engage in SDM in clinical contexts (including prenatal screening) [ 44 ]. Interestingly, some of our previous work has shown that pregnant women also have high levels of intention to use a DA for Down syndrome screening decisions [ 29 , 45 ]. Together, these results suggest that both health professionals and pregnant women seem inclined to use a DA in Down syndrome prenatal screening, and that lack of intention among either health professionals or pregnant women is not the cause of failure to implement DAs in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by our team (referred to hereinafter as the Delanoë study), 31% of pregnant women had little intention to use PtDAs for DS prenatal screening (i.e. their intention was “weak” or “neutral”) [ 16 ]. Intention is defined as a conscious decision to perform a behaviour, a resolution to act in a certain way or an impulse for purposeful action [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To be eligible, women had to: (a) be at least 18 years old; (b) be more than 16 weeks pregnant (we did not want to influence the outcome of their decision, and in Quebec, at 16 weeks women will have already taken the public screening test or refused it); or having given birth in the previous year; (c) be able to speak and write in French or English; (d) be able to give informed consent. We excluded women who: (i) participated in certain phases of our earlier studies on DAs (30,31) and/or (ii) presented a high-risk pregnancy (e.g. preeclampsia, gestational diabetes, multiple pregnancy).…”
Section: Participants and Recruitmentmentioning
confidence: 99%